Explorasi Masyarakat Lokal dalam Pengembangan Desa Wisata - I Nyoman Gede Agus Jaya Saputra; Agus Fredy Maradona (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2020)
One form of community based tourism that is currently being developed by the government in maintaining the preservation of local culture Nongan Tourism Village has been running the development program from 2014 together with the decree of Karangasem Regent NO / 658 / HK / 2014 together with the formation of pokdarwis in the framework of development Tourism through PNPM Mandiri, This study discusses the form of local community participation as well as the benefits of the pa-klipasi obtained in the development of Nongan Tourism Village in Karangasem Regency. This research was conducted in Nongan Tourism Village, in Rendang District, Karangasem Regency with the aim to know the shape and the benefit of participation in Nongan Tourism Village development. Data were obtained through questionnaires distributed to respondents consisting of 100 local people of Nongan Tourism Village by using accidental sampling. The collected data is analyzed qualitatively by using Likert Scale. The result of the analysis shows that the participation of local community in the development of Nongan Tourism Village are 3 forms, namely participation of mind, participation of personnel, participation of property, while the form of skills participation and skill with social participation of local community is never. While the benefits of community participation derived from the development activities Nongan Tour Village more socio-cultural benefits perceived by the community directly involved from the development activities Nongan Tourism Village Another perceived benefit is from economic benefits and environmental benefits in the form of interaction with tourists and support programs that Done by the government.